If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -16 = 3x Reorder the terms: -16 + 7x = 3x Solving -16 + 7x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + 7x + -3x = 3x + -3x Combine like terms: 7x + -3x = 4x -16 + 4x = 3x + -3x Combine like terms: 3x + -3x = 0 -16 + 4x = 0 Add '16' to each side of the equation. -16 + 16 + 4x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 4x = 0 + 16 4x = 0 + 16 Combine like terms: 0 + 16 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 15=-5t^2+22t+15 | | (-1+x)(-1+x)=0 | | 4x+4-3x=13 | | c^2+18c=0 | | 13+(-12)-(-5)= | | 13y-4-14y=16+3y-12 | | 12=-5t^2+11t+12 | | 0=-16t^2+64t+4 | | s=-16t^2+64t+4 | | -6q+13-3q=17-q-20 | | 4m-21=2m+5 | | 5x^2-17x+6=9 | | 81=30-17n | | 7y-15-4y=-18 | | 17=-3r-7 | | 17=3r-7 | | -2(m+6m)-6=-4(m+6)-4m | | 5x^2+18x-24=0 | | 4(6-0.5y)+2y=24 | | -p^2+13p+42=0 | | 3x+9=6x+12 | | 1=4a+(-8)+2a+1-a-(-4+a) | | t^2-26t+25=0 | | 2x+7=-6(2-6x) | | s=-16t^2+1444 | | 4x^3+7x^2-2x=0 | | Q-3=5 | | 7x^3+2x^2-2x=0 | | 24=3y+21 | | 6y-20=2y-16 | | 2x^3-8x^2+6x=0 | | -3s-s+10=0 |